2000
DOI: 10.1016/s0029-7844(00)00954-6
|View full text |Cite
|
Sign up to set email alerts
|

Oral misoprostol and intracervical dinoprostone for cervical ripening and labor induction: a randomized comparison

Abstract: A single dose of 200 microg oral misoprostol was more effective for cervical ripening and labor induction than 0.5 mg of dinoprostone intracervically every 6 hours, with a maximum of four doses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 12 publications
6
15
0
1
Order By: Relevance
“…The finding of our study was consistent with findings reported by Mundel and young and Bartha et al 7,8 No. of doses…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The finding of our study was consistent with findings reported by Mundel and young and Bartha et al 7,8 No. of doses…”
Section: Discussionsupporting
confidence: 94%
“…The finding of our study was consistent with findings reported by Mundel and young and Bartha et al 7,8 Bishop's score at induction statistically not significant in both the groups. 92.5% (37) patients of misoprostol group had unfavourable cervix as compared to 100% (40) pts in cervigel group.…”
Section: This Comparativesupporting
confidence: 93%
“…6,7,8 In study done by Kulshreshtha S et al the mean preinduction Bishops score was 4.45±1.77 in PGE1 and 4.25±1.89 in PGE2 group and in our present study the mean pre-induction Bishops score was 3.46±1.23 in PGE1 and 3.36±1.1 in PGE2 group. 5 In studies done by Bartha et Incidence of caesarean sections was high in PGE2 group compared to PGE1 group in studies done by Bartha L et al, Patil Kamal P et al, Kulshreshtha S et al 3,4,9 Present study showed high caesarean section rate in PGE1 group compared to PGE2 group in accordance with study done by Parmar M et al, but it was not statistically significant. 6 Liquor colour at delivery was meconium stained in 12% in PGE1 group and 6% in PGE2 group in study done by Patil P et al10.In our study it was 16% in PGE1 and 8% in PGE2 group which was comparable.…”
Section: Resultssupporting
confidence: 75%
“…Parmar M et al study showed 40% and 36% cases, Greagsons et al study 95% and 94%, Sheela CN et al study 36% and 32% cases induced for postdatism in Group I and Group II respectively. [6][7][8] Incidence of caesarean sections was high in PGE2 group compared to PGE1 group in studies done by Jose BL et al4, Kamal P et al, Kulshreshtha S et al [3][4][5] Present study showed high caesarean section rate in PGE1 group compared to PGE2 group in accordance with study done by Parmar M et al but it was not statistically significant. 6 Liquor colour at delivery was meconium stained in 12% in PGE1 group and 6% in PGE2 group in study done by Patil P et al 9 In present study it was 16% in PGE1 and 8% in PGE2 group which was comparable.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, in study done by Jose BL et al the mean age in both the groups is 28.31±5.09 and 28.12±4.66 and in Kulshreshtha S et al study the mean age is 20±3.75 and 25.35±3.31 in two groups respectively and the distribution in age in two groups was not statistically significant. 4,5 In present study postdatism was the most common indication for induction, 70% and 64%in Group I and Group II respectively. Parmar M et al study showed 40% and 36% cases, Greagsons et al study 95% and 94%, Sheela CN et al study 36% and 32% cases induced for postdatism in Group I and Group II respectively.…”
Section: Discussionmentioning
confidence: 46%